Relative energy deficiency in sport and the role of ultrarunning coaches according to two female ultrarunners - Stewart, D. G.; Allen, J. B.; Kirkland, A. (International Journal of Sports Science & Coaching, 2023)
Relative Energy Deficiency in Sport (RED-S) is a complex syndrome that occurs as a result of prolonged Low Energy Availability (LEA) leading to health and performance impairments. However, whilst the coach plays an important role when working with athletes with RED-S, no research exists specifically exploring their role. Therefore, this study investigates the role of the coach from the athletes` perspective within an ultrarunning context. Ultrarunners are at risk of LEA due to large training volumes and record high incidences of psychological and physiological conditions linked to RED-S, such as disordered eating and bone stress injuries. Two female ultrarunners who had experience with RED-S each participated in three semi-structured interviews. The findings highlight the multifaceted role of the coach which changes depending on the stage of the athletes` RED-S Journey. Of primary importance was that the coach should be educated on RED-S in order to provide value throughout. Secondly, for effective recovery, the coach should embrace working with a multidisciplinary support team of experts. Thirdly, the coach should actively work on establishing strong relationships with the athlete and their support network. This will propagate trust and honest conversations, a key requirement for recovery from, and ongoing training post, RED-S.